The youth-caregiver relationship quality in residential youth care: Professionals perceptions and experiences - Magalhães, Eunice (2023)
This study aimed to explore the perceptions and experiences of professionals working in residential care (RC) settings (i.e., caregivers and directors) about youth-caregiver relationship quality (YCRQ). Method: A qualitative study was developed in Portugal including 15 caregivers (73.3% women, 23–50 years) and 15 directors (73.3% women, 34– 45 years) working in 18 generalist RC units. Data were collected through six focus groups using a semi-structured interview script. Data were analyzed following a content analysis approach using NVIVO 12 software. Results: Our findings revealed that the concept of YCRQ in RC was mainly described in terms of good qualities, and the organizational determinants of YCRQ relationships were most mentioned both by caregivers and directors (i.e., organizational social context, intervention models and strategies). Individual characteristics of youth and staff were less described as determinants of YCRQ. These findings provide important insights for practice. Conclusions: efforts should be made to design interventions in RC that aim to improve its organizational social climate so as to provide caregivers with the necessary support and resources that enable them to enhance positive YCRQ.